57.0k views
0 votes
Simplify
3x - 7- (4x^2 - 2x-5)​

User Pindo
by
5.3k points

1 Answer

3 votes

For this case we must simplify the following expression:


3x-7- (4x ^ 2-2x-5)

According to the law of multiplication signs we have:


- * + = -\\- * - = +

So, we have:


3x-7-4x ^ 2 + 2x + 5 =

We add similar terms:


3x + 2x-7 + 5-4x ^ 2 =

Equal signs are added and the same sign is placed.

Different signs are subtracted and the major sign is placed.


5x-2-4x ^ 2 =

We order the expression:


-4x ^ 2 + 5x-2

ANswer:


-4x ^ 2 + 5x-2

User Martin Fasani
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.